Application of engineering ductile tearing simulation method to CRIEPI pipe test. (March 2016) - Nam, Hyun-Suk; Oh, Young-Ryun; Kim, Yun-Jae; Kim, Jong-Sung; Miura, Naoki
Abstract: A method to simulate ductile tearing in large-scale pipes using finite element analysis is proposed, based on the stress-modified fracture strain model. An element-size-dependent critical damage model is also introduced in damage simulations. The damage model and associate parameters are determined from tensile and fracture toughness test data. The method is applied to simulate five bending tests of circumferential cracked carbon steel pipes. Simulated results agree overall well with two through-wall cracked pipe test data, but consistently over-predict the maximum loads for three surface cracked pipe tests. Advantages of the proposed method in practical application is briefly discussed.